A mitochondrion-targeting tanshinone IIA derivative attenuates myocardial hypoxia reoxygenation injury through a SDH-dependent antioxidant mechanism. (14th September 2019) - Zhao, Yun-Peng; Wang, Fei; Jiang, Wei; Liu, Jinfeng; Liu, Bao-Lin; Qi, Lian-Wen; Zhou, Wen
Abstract: The medicinal values of many natural bioactive components to treat myocardial ischaemia reperfusion (I/R) injury are limited by their poor permeability. Herein, we demonstrate that an original tanshinone IIA derivative (Tan-TPP) could probably be improved myocardial I/R injury suppressant. It was optimised by mitochondria targeting group triphenylphosphine (TPP). Intriguingly, it could accumulate in mitochondria to more efficiently inhibit the activity of succinate dehydrogenase (SDH), which is closely related with I/R oxidative injury. Moreover, by inhibiting SDH activity, it could better prevent excess intracellular reactive oxygen species production to reduce oxidative damage, and regulate ATP levels to ensure energy output. Consequently, mitochondria targeting tanshinone IIA derivative Tan-TPP is a new type candidate for the treatment of myocardial I/R injury through an SDH dependent antioxidant mechanism.